A Management of Electrolyte Disorders - Termiko, Edi; Meutia, Sri (PT FORMOSA CENDEKIA GLOBAL, 2025)
There are several electrolytes that are important in maintaining homeostasis systems including sodium (Na+), potassium (K+), calcium (Ca2+) and magnesium (Mg2+). Electrolytes are essential for basic life functions, such as maintaining electrical neutrality in cells and generating and conducting action potentials in nerves and muscles. Electrolyte needs can come from food and fluids consumed. The amount of electrolytes can become unbalanced, causing high or low levels. Electrolyte imbalance is a serious condition that can have a significant impact on human health. Correct diagnosis of any electrolyte disorder requires a thorough understanding of the clinical symptoms and relevant laboratory tests. Careful management is needed to correct electrolyte imbalances and prevent serious complications